2013 Agricultural Research Southeast Agricultural Research Center - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2013)
At head of title: SEARC Agricultural Research Southeast Agricultural Research Center 2013
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1087; Kansas Agricultural Experiment Station contribution; no. 13-281-S; Beef cattle; Forage crops; Soil management; Water management